Efficient Multimedia Data Storage in Cloud Environment - Deshpande, Prachi; Sharma, S. C.; Peddoju, Sateesh K.; Abraham, Ajith (Informatica, 2015)
With the rapid adoption of social media, people are more habituated to utilize the images and video for expressing themselves. Future communication will replace the conventional means of social interaction with the video or images. This, in turn, requires huge data storage and processing power. This paper reports a compression/decompression module for image and video sequences for the cloud computing environment. The reported mechanism will act as a sub module of IaaS layer of the cloud. The compression of the images was achieved by means of redundancy removal using block matching algorithm. The proposed module had been evaluated with three different video compression algorithms and variable macroblock size. The experimentations were carried out on a cloud host environment by using VMWare work station platform. Apart from being simple in execution, the proposed module does not incur an additional monetary burden, hardware or manpower to achieve the desired compression of the image data. Experimental analysis has shown a considerable reduction in data storage requirement as well as the processing time.